In-situ combustion - a thermal method in enhanced oil recovery - Derahman, Mohd. Nawi (Faculty of Chemical & Natural Resources Engineering, 1989)
Enhanced Oil Recovery, EOR, is the future for oil industry. Any technique of EOR that could increase the total recovery factor by 10% would increase the amount of recoverable oil reserve by 50%. In-situ combustion is one such technique that is applicable to both heavy and light oil reservoirs. The recovery factor by this method is high. This paper explains the benefits of thermal recovery and describes the types of in-situ combustion process.